Motivation, Professionalism, and Language Skills: An Analysis of the PPG Prajabatan Program in Indonesia: Irma Fitriani*, Ryan Cipta Julianda, Dian Ratna Sari - Fitriani, Irma; Julianda, Ryan Cipta; Sari, Dian Ratna (JPGENUS: Jurnal Pendidikan Generasi Nusantara, 2023)
PPG Prajabatan asserts its efficacy in conferring benefits upon educators; however, a considerable number of participants express dissatisfaction with the training's effectiveness. The objective of this study is to scrutinize students' perspectives regarding the influence of PPG Prajabatan on motivation, professionalism, and linguistic aptitude. Online surveys and interviews were deployed to elicit comprehensive insights from participants. Findings reveal participants' comprehension of the subject matter, yet their engagement in training and leadership involvement necessitate refinement. The program exhibits constraints in augmenting language proficiency. Activities such as discussions and presentations are empirically proven to be more efficacious than traditional lectures. A critical review of training materials is imperative to ensure sustained participant motivation and self-enhancement. Recommendations advocate for the incorporation of activities fostering both local and foreign language proficiency within the framework of the PPG Prajabatan program.